A Computer-Assisted Educational Auction Simulation. (June 2014) - Noy, Avraham
Background: Internet auctions are popular mechanisms to conduct electronic-business transactions. Because they have received a significant attention, auction simulations have spread to a variety of domains. Aim: The aim of this article is to examine participation in aneducational Internet auction simulation andanalyze participants'behavior andattitude . Method: Forty-eight students participated in twoauction simulation sessions. Data were collected during the exercise, and questionnaire results were analyzed. Results: Findings reveala long-tail distribution of participation among users. Participants use the simulation mostly inlatter phases . Participants' performance was affected by theintensiveness of participation . Conclusion: Long-duration simulations with voluntary participation provide benefits to enthusiastic participants and may suffer fromprocrastination tendency .